2020
DOI: 10.2478/agri-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Different Organic and Inorganic Fertilisers on Soil Fertility, Plant Growth, Soil Microbial Community, and Storage Ability of Lettuce

Abstract: The current study was conducted to assess whether organic fertilisation could replace mineral fertilisation in lettuce production without adverse effects on yield, quality, and postharvest behaviour. The effect of either mineral or organic fertiliser on soil fertility or the microbial community was also studied. Control plots were fertilised with recommended rates of mineral fertiliser (150: 45: 65 kg/ha NPK) and the other treatments were 15 t/ha compost, 10 t/ha rabbit manure, and 10 t/ha chicken manure. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Chinensis (Table 2), and these results were consistent with the results of previous studies (Xu et al, 2002;Li et al, 2017;Youssef and Eissa, 2017;Serri et al, 2021). Consistent with the results of our study (Table 3), previous research also found that organic fertilization significantly increased soil organic carbon, total nitrogen, total phosphorus and pH (Li X. et al, 2021), and chemical fertilization decreased soil pH (Li et al, 2019), but rabbit manure fertilizer increased soil EC compared to chemical fertilization (El-Mogy et al, 2020). Rabbit manure fertilizer decreased the nitrate content of Brassica rapa var.…”
Section: Discussionsupporting
confidence: 92%
“…Chinensis (Table 2), and these results were consistent with the results of previous studies (Xu et al, 2002;Li et al, 2017;Youssef and Eissa, 2017;Serri et al, 2021). Consistent with the results of our study (Table 3), previous research also found that organic fertilization significantly increased soil organic carbon, total nitrogen, total phosphorus and pH (Li X. et al, 2021), and chemical fertilization decreased soil pH (Li et al, 2019), but rabbit manure fertilizer increased soil EC compared to chemical fertilization (El-Mogy et al, 2020). Rabbit manure fertilizer decreased the nitrate content of Brassica rapa var.…”
Section: Discussionsupporting
confidence: 92%
“…In this situation, the changes in applied organic fertilizer and released N, K and Ca in soil are relaying on the manure type and soil traits (Hernández et al 2016). Furthermore, organic fertilizers have soil microbial content and activity higher than chemical fertilizers (El-Mogy et al 2020). These findings might be linked with the amounts of organic carbon in various organic fertilizers (Chakraborty et al 2011;Amalraj et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Organic fertilizers are known to improve the physical, chemical, and biological properties of soils. These fertilizers, including rabbit manure, increase the content of organic matter 15 , pH, cation exchange capacity 20 , organic carbon content in soil, total fungi, and bacteria 21 . The use of manure as fertilizer increases the yield and quality of crops, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of manure as fertilizer increases the yield and quality of crops, e.g. the content of protein and minerals 15 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%